Prevalence and Antibiotic Susceptibility of Pathogenic Enterobacteria Strains from Three Biotopes in the City of Ouagadougou (Burkina Faso) - Dabiré SC; Somda MK; Nitièma LW; Kambiré D; Kiemtoré S; Soubeiga ST; Zouré AA; Yao KKT; Compaoré TR; Ouedraogo HG; Dicko MH (Infection and Drug Resistance)
Sanhitouo Charlemagne Dabiré,1,2 Marius K Somda,2 Léon W Nitièma,3 Dinanibè Kambiré,1 Samiratou Kiemtoré,1 Serge Théophile Soubeiga,1 Abdou Azaque Zouré,1 Konan Kouakou Toussaint Yao,2 Tegwindé Rebeca Compaoré,1 Henri Gautier Ouedraogo,1 Mamoudou H Dicko2 1Département Biomédical et Santé publique, Institut de Recherche en Sciences de la Santé ́(IRSS)/Centre National de la Recherche Scientifique et Technologique (CNRST), Ouagadougou, Burkina Faso; 2Département de Biochimie Microbiologie, Ecole Doctorale Sciences Et Technologies (EDST)/Université Joseph KI-ZERBO, Ouagadougou, Burkina Faso; 3Institut de l’Environnement et de Recherches Agricoles (INERA), Centre National de la Recherche Scientifique et Technologique (CNRST), Ouagadougou, Burkina FasoCorrespondence: Sanhitouo Charlemagne Dabiré, Email charlemagne_dabire@yahoo.frPurpose: The emergence of antibiotic resistance in pathogenic Enterobacteriaceae is a public health problem in tropical countries such as Burkina Faso. Antibiotic resistance could be identified using a variety of approaches. This study aimed to estimate the prevalence of pathogenic enterobacteria strains from three sources, as well as their antibiotic resistance profile to biotope and climatic season.Material and Methods: The methodological approach consisted of identifying Enterobacteriaceae from human (urine, stool), animal (eggs, milk, fish), and environmental (soil, lettuce) samples, followed by assessing their antibiotic susceptibility. Samples were collected from February to December 2023. Bacterial species were isolated and phenotypically identified (morphologically, culturally, biochemically, and antigenically) using standard methods. The prevalence of bacterial susceptibility to ten antibiotics was determined using the agar disk diffusion method. The collected data were analyzed with IBM SPSS Statistics 25 software.Results: A total of 615 Enterobacteriaceae isolates were collected, including 300, 168, and 147 samples from human, animal, and environmental sources respectively. Phenotypic characteristics allowed to partially identify 43 species, among these 29.76% belonged to Escherichia coli, 24.72% to Enterobacter cloacae, 13. 82% to Klebsiella pneumoniae, 3.41% to Enterobacter sakazakii and 2.6% to Klebsiella oxytoca. Bacterial resistance rates were: aminopenicillins (54.8%), first-generation cephalosporins (35.3%), sulfonamides (33.3%), third-generation cephalosporins (30.7%), fourth-generation cephalosporins (22.5%), fluoroquinolones (21.8%), phenicols (16.8%), and carbapenems (16.2%). The distribution of antibiotic resistance was 45.3% from human sources, 19.3% from animal sources, and 13.8% from environmental sources.Conclusion: The results indicate that resistant bacteria can come from any of the three biotopes, with human origin being the most frequent. The high prevalence of resistance to the antibiotics tested in isolated bacteria raises interest in investigating the genetic factors responsible.Keywords: pathogenic Enterobacteriaceae, biotopes, resistance, antibiotics, Burkina Faso